Fungsi Multimedia dalam Pembuatan Setting dalam Pertunjukan Ketoprak Modern - Wisnu Samodro (Lembaga Pengembangan Kinerja Dosen, 2025)
Ketoprak as a form of traditional Javanese theater has the characteristics of historical storytelling or legend supported by artistic elements such as music, dialogue, clothing, and stage settings. In its development towards a modern form of ketoprak, the use of multimedia technology has become one of the significant innovations, especially in the creation of performance settings. This article examines in depth the function of multimedia in supporting the creation of modern ketoprak settings, both from aesthetic, dramatic, and production efficiency aspects. This study uses a qualitative descriptive method with data collection through observation of ketoprak performances that integrate multimedia, in-depth interviews with directors, artistic stylists, and multimedia technicians, and literature studies that discuss contemporary performing arts. The results of the study show that multimedia plays an important role in building richer imaginative atmospheres and spaces and allows for the depiction of complex settings such as palaces, forests, or battlefields quickly and effectively. In addition, multimedia expands visual possibilities through projection of images, videos, and dynamic light effects that cannot be achieved with traditional physical properties alone. The multimedia function has also been proven to enhance the viewer experience by presenting a more modern visual sensation without losing the traditional identity of ketoprak. These findings indicate that multimedia serves not only as a complement, but also as an integral element that influences the overall aesthetic, reinforces dramatic messages, and facilitates transitions between scenes.